A hierarchical approach to 3D non-parametric surface relief completion - Breckon, Toby P.; Fisher, Robert B. (Elsevier Science B.V., Amsterdam., 2012)
Typical stereo and laser scan based 3D acquisition approaches are essentially limited to 2.5D capture. The resulting 3D completion problem, to derive missing information in 2.5D scenes from limited contextual information, has received increasing attention in literature. Here we propose a hierarchical extension to our recent non-parametric approach for the 3D completion of surface relief detail to allow the resolution of inconsistencies arising in the global structure of an area completed with this technique. We test our approach over a range of surface types and contrast the presence of global discontinuities in the resulting completion with those of the earlier approach.
Keywords: relief completion, amodal completion, volume completion, visual completion, perceptual completion, surface completion